KAJIAN SEMANTIK TENTANG RUH ANTARA MAKNA ILAHI DAN KEMANUSIAAN - Fadhoil Khair; Abd. Hamid; Nur Khalil; Jazari Ibnu Abbas (LPPM IAI Hasanuddin Pare-Kediri, 2026)
This research is motivated by a highly significant debate regarding the nature of ruh (spirit/soul) in the Qur'an, which frequently falls into logical fallacies, being regarded merely as a divine mystery, or suffering from fatal misconceptions between the meanings of life (soul) and revelation in various classical and modern exegeses. Therefore, this study aims to map out the comprehensive understanding of the meaning of ruh in the Qur'an in detail, emphasizing the divine and human dimensions to avoid a partial understanding. To achieve this objective, this library research applies Toshihiko Izutsu’s semantic approach to the Qur'an. The analysis is specifically designed to explore basic and relational meanings through syntagmatic and paradigmatic analyses to reconstruct the Qur'anic worldview (Weltanschauung) regarding the term. The results indicate that the word ruh is repeated 24 times in the Qur'an and originates from the root word ra-wa-ha, which means to go or to move, and shares a close semantic relationship with the word rih (wind). Relationally, the meaning of ruh is classified into two major categories: the divine dimension, manifested as revelation, the absolute affair of Allah, and the embodiment of Angel Jibril; and the human dimension, acting as an essential spiritual element that provides life, inner consciousness, and morality to the human physical body. Through paradigmatic analysis, the concept of ruh is proven to interact dynamically in shaping a holistic structure of human identity through its functional relationships with the terms nafs (soul), wahyu (revelation), qalb (heart), ‘aql (intellect), and hayah (life).